How to Stop Time - Haig, Matt, 1975- ([New York] : Penguin Books, an imprint of Penguin Random House LLC, 2019)
Tom Hazard has just move back to London to settle down and become a history teacher. But while he may look like an ordinary forty-one-year-old, owing to a rare condition, hes been alive for centuries. Unfortunately for Tom, the Albatross Society, the secretive group that protects people like him, has one rule: Never fall in love.
Keywords: Secret societies -- Fiction; Immortality -- Fiction; Man-woman relationships -- Fiction; London (England) -- Fiction; Fiction; Romance fiction; Romance fiction